Decolonize Knowledge and See the Postsocialist "Other" : Review on Tlostanova, M., 2017, Postcolonialism and Postsocialism in Fiction and Art. London: Palgrave Macmillan Cham. - Котляр, Олександра (Київський національний університет імені Тараса Шевченка, 2022)
The essay considers approaches to understanding the current situation of the former socialist countries, proposed by the decolonial researcher Madina Tlostanova in her 2017 work «Postcolonialism and Postsocialism in Fiction and Art». The eight chapters of Tlostanova's book analyze specific temporal and spatial relationships that define both the postsocialist cultural and political context. Tlostanova notes the impossibility of applying the terminology that has been integrated into Western scientific discourse since the Cold War to the postsocialist space. Such an approach automatically places the postsocialist countries in the post-bipolar hierarchy of the world built by the West. The article's author compared the basis of Tlostanova's research with the approaches of other colonialism and imperialism researchers, such as John McKenzie, Touraj Atabaki, Saurabh Dube, and Ramon Grosfoguel. In my opinion, they can expand the theoretical model formulated by Tlostanava. Tlostanova criticizes postcolonial optics as a paradigm leaving the countries of the former «Socialist Camp» behind a new, but already epistemological «Iron Curtain» and continuing to reproduce colonial narratives. In the book, Tlostanova considers postsocialism as a special state, marked by the intersection of multiple post-dependencies — Russian, post-soviet, post-dictatorship, as well as global coloniality. A symptom of global coloniality is, in particular, the phenomenon of self-colonization. This phenomenon manifests itself in self-exoticization through the transformation of folk culture into a commodity, unhealthy nostalgia for the past, historical memory distortion, and instrumentalization of images of the past. Tlostanova explains this recursiveness of the postsocialist space through the concept of tempo-localities, which are most clearly traced in art. Thus, decolonial artistic practices in a post-dependent society forms a sensual basis for art and knowledge decolonization in general.

У статті авторка розглядає підходи до осмислення сучасного становища колишніх соціалістичних країн, запропоновані деколоніальною дослідницею Мадіною Тлостановою у праці 2017 р. «Постколоніалізм і постсоціалізм у художній літературі та мистецтві». Вісім розділів книжки М. Тлостанової — це аналіз особливих часових і просторових відносин, які визначають як постсоціалістичний культурний, так і політичний контекст. М. Тлостанова зауважує на неможливості застосування до постсоціалістичного простору термінології, інтегрованої у західний науковий дискурс з часів Холодної війни, який автоматично відводить постсоціалістичним країнам місце у розбудованій Заходом постбіполярній ієрархії світу. Авторка статті порівняла засади її дослідження з підходами інших дослідників колоніалізму та імперіалізму (як то Джон Маккензі, Саурабх Дубей, Турадж Атабакі, Рамон Гросфогель), якими може бути розширена теоретична модель, сформульована М. Тлостановою. Постколоніальну оптику М. Тлостанова критикує як таку, що залишає країни колишнього «соціалістичного табору» за новою, проте вже епістемічною «залізною завісою» і продовжує відтворювати колоніальні наративи. У книзі М. Тлостанова розглядає постсоціалізм як особливий стан, означений перетином множинних постзалежностей — російської, пострядянської, постдиктатурної, а також глобальної колоніальності. Симптомом останньої є, зокрема, явище самоколонізації, що проявляється в самоекзотизації через перетворення народної культури на товар, нездоровій ностальгії за минулим, викривленні історичної пам’яті та інструменталізації образів минулого. Таку рекурсивність постсоціалістичного простору М. Тлостанова пояснює через концепцію темполокальностей, які найбільш виразно проявляються у мистецтві. Деколоніальні мистецькі практики у постзалежному суспільстві, таким чином, формують чуттєве підґрунтя для деколонізації  й знання загалом.
Деколонізувати знання і побачити постсоціалістичного «Іншого»: Tlostanova, M., 2017, Postcolonialism and Postsocialism in Fiction and Art. London: Palgrave Macmillan Cham.
Keywords: постколоніалізм; постсоціалізм; постзалежність; глобальна колоніальність; темполокальності; самоколонізація; деколоніальне мистецтво; Мадіна Тлостанова.; postcolonialism; postsocialism; post-dependence; global coloniality; tempo-localities; self-colonization; decolonial art; Madina Tlostanava